Data Sheet 1_Evaluation of clinical, analytical, and genotyping performance of Hex L1 real-time PCR coupled with high-resolution melting curve analysis for fowl adenovirus outbreak investigation in Morocco.xlsx - Amina Kardoudi (22686524) (2025)
Fowl adenoviruses (FAdVs) are widespread viruses in poultry populations, responsible for several severe diseases, including Inclusion Body Hepatitis (IBH), Adenoviral Gizzard Erosion (AGE), and Hepatitis-Hydropericardium Syndrome (HHP). These diseases have been associated with significant economic and health impacts on poultry industries. Accurate detection and genotyping play a key role in the diagnosis of these infections, as different FAdV genotypes are associated with distinct disease syndromes and epidemiological patterns. In this study, we aimed to evaluate the clinical, analytical, and genotyping performance of the Hex L1 PCR combined with High-Resolution Melting (HRM) Curve analysis for investigating recent IBH and AGE outbreaks in Morocco. The study involved 26 clinical samples collected from broiler and layer poultry farms suspected with IBH or AGE. These samples were amplified using conventional PCR, real-time PCR/52 K test, and the Hex L1 PCR/HRM test. Field samples were also sequenced and compared with HRM curve analysis results to validate the genotyping accuracy of the Hex L1 PCR/HRM method. Phylogenetic analysis of the sequenced samples revealed several FAdV genotypes, including FAdV-11 and FAdV-8b in IBH cases, and FAdV-1 and FAdV-8a in AGE cases, highlighting the genetic diversity of circulating strains. The Hex L1 PCR/HRM method successfully amplified all 12 FAdV serotypes, demonstrating excellent reproducibility and repeatability, with coefficients of variation ranging from 0.19% to 1.82%. Moreover, this method showed a strong correlation with the real-time PCR/52 K test, achieving a high correlation coefficient of 0.9077. The HRM curve analysis accurately genotyped all the field samples, with results consistent with sequencing outcomes. In conclusion, this method provides a fast, sensitive, and reliable alternative for FAdV detection and genotyping. It enables universal detection, quantification, and genotyping in a single step, overcoming the limitations of traditional techniques, making it an ideal tool for sample screening, while sequencing validation is necessary for confirmation.